Towards a better understanding and new tools for soft fruit quality control - Gine Bordonaba, Jordi (Cranfield University, 2010)
Prospects for the production of new and more tasteful strawberry and blackcurrant fruits may be achieved not only through genetic improvement and release of new varieties but also by adapting current cultivation systems and boosting the development of diagnostics tools for better quality control (QC) by growers and breeders. The balance between sugar and acid content (S/A ratio) and even the content of certain health-related compounds within the fruit, may act as important indices of consumer acceptability or overall berry quality. The S/A ratio, of fruits from 23 blackcurrant and 19 strawberry cultivars ranged from 1.84-4.39 and 3.9-9.6, respectively. S/A ratios generally increased during blackcurrant ripening (up to 1.3-fold higher for certain cultivars), declined slightly during postharvest storage at different temperatures or even changed when the same cultivar was grown at different locations (up to 30% of variation). Synthesis of health-related compounds (i.e. anthocyanins) occurred even after harvest and was strongly influenced by storage temperature and maturity at harvest. Deficit irrigation (DI) at different fruit developmental stages, was investigated as a potential strategy to improve strawberry fruit quality in a range of cultivars. The S/A ratio and the concentration of health-related compounds (viz. individual anthocyanins, antioxidant capacity) were much greater (i.e. 1.4-fold higher antioxidant capacity), for some cultivars, in fruits from DI-treated plants as compared with fully irrigated plants. The taste- and health-related composition of both blackcurrant and strawberries considerably changed from year-to-year demonstrating the influence of agroclimatic conditions on overall fruit quality. Cont/d.